Saving Private Money - Maseleno, Andino (2019)
The savings and cash withdrawal application information system that runs on the new Bandung BMT el-ihsan KJKS it is still conventional so there are several problems in handling the process of presenting financial reports include delays in service to customers, and often occur reporting and recording errors. The main objective of this research is to present the system. Information in the form of applications that can be used to suit your needs. New system design using structured techniques where the system is modeled with a data flow diagram, database modeled using Entity Relationship Diagram (ERD). Input application creation savings and cash withdrawals in the new KJKS BMT el-ihsan Bandung using a programming language dhelphi 7 and ms access database. This research produces applications for savings and drag inputs cash, and with a new system can optimize the computer system in the process service to customers and reporting so that they can manage data well, for produce information that is easier and more accurate.